Curriculum of Management in Improving the Quality of Catholic School Education in Samarinda City, East Kalimantan, Indonesia - Warman Warman; Lorensius Lorensius; Rohana Rohana (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to describe curriculum management in improving the quality of education in Catholic schools in Samarinda City, East Kalimantan Province, Indonesia. This study uses a qualitative approach with a descriptive method. Observation, documentation, and interview techniques were used to obtain data related to curriculum management in improving the quality of Catholic education by involving foundation administrators, school principals, vice-principals, curriculum fields, and teachers. The collected data were analyzed in the form of data reduction, data presentation, drawing conclusions, and checking the validity of the data by using technical triangulation methods. The results of this study found that educational curriculum planning in improving the quality of education in Catholic schools always emphasizes the importance of aspects of the school's vision and mission, changes that occur in the education process, and is adjusted to the national education curriculum program and local content curriculum, school circumstances and needs. Curriculum organization is carried out by assigning duties and authority by the principal to the curriculum coordinator, namely the vice principal, and to senior teachers to supervise the learning process. In addition, through classroom supervision, teacher performance is assessed in the learning process. Good curriculum management, it can be a roadmap to achieve effective and efficient learning, build student character, improve learning achievement, and ultimately improve the quality of education.